2011
DOI: 10.1111/j.1365-2710.2011.01290.x
|View full text |Cite
|
Sign up to set email alerts
|

Improvement of tardive dyskinesia and dystonia associated with aripiprazole following a switch to quetiapine: case report and review of the literature

Abstract: There were several previous case reports on dyskinesia and dystonia associated with aripiprazole medication. The risk factors for tardive dyskinesia include older age and female sex. However, our case was a male patient who was younger compared with the previous cases and so should have been less at risk for dyskinesia in comparison with the previous cases. The effects of aripiprazole can include tardive movement disorders. Dyskinesia, dystonia and psychotic symptoms were improved with relatively small dose of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 24 publications
1
9
0
Order By: Relevance
“…Risperidone demonstrated a much higher tolerability, as 33% (7/21) of the aripiprazole treated patients dropped out before the end of the 22‐day trial (0% drop out for risperidone, 0/21). Treatment with aripiprazole resulted in significantly more akathisia and agitation in patients, contradicting biologically expected results, but consistent with a growing body of literature (Ono et al, ; Samiei et al, ). Surprisingly, although both risperidone and aripiprazole reduced cravings, the effect was significantly greater in risperidone‐treated subjects.…”
Section: Treatment Of Mapsupporting
confidence: 64%
“…Risperidone demonstrated a much higher tolerability, as 33% (7/21) of the aripiprazole treated patients dropped out before the end of the 22‐day trial (0% drop out for risperidone, 0/21). Treatment with aripiprazole resulted in significantly more akathisia and agitation in patients, contradicting biologically expected results, but consistent with a growing body of literature (Ono et al, ; Samiei et al, ). Surprisingly, although both risperidone and aripiprazole reduced cravings, the effect was significantly greater in risperidone‐treated subjects.…”
Section: Treatment Of Mapsupporting
confidence: 64%
“…The suppressive effects of first-generation neuroleptics on TD can be substantial (>60 % improvement), but several studies have suggested that this is only a temporary effect [25,59], triggering a spiraling of the dose upwards over time. The SGAs quetiapine, clozapine, risperidone, and olanzapine [60][61][62][63][64] have also been used to treat TD with similarly unknown efficacy and safety in the long term [21]. Other long-term studies do not support the ability of SGAs to suppress TD [46].…”
Section: Should Neuroleptics Be Used As a Therapeutic Agent For Td?mentioning
confidence: 99%
“…Quetiapine-related TD was noted and described in an early case report about 15 years ago 5). However, some reports also mention contrary findings of quetiapine's ability to relieve TD 1,2,8,9,10,11,12,13). Emsley et al14) found that quetiapine could effectively reduce TD severity in patients with established TD, but the mechanism of this action is unclear.…”
Section: Discussionmentioning
confidence: 99%